Diabetes and smoking as predictors of cancer in Indigenous adults from rural and remote communities of North Queensland – A 15‐year follow up study. Issue 5 (16th April 2018) - Li, Ming; Roder, David; McDermott, Robyn
Abstract : Indigenous Australians generally have a poor health status and an elevated cancer mortality that has increased in recent decades. A cohort of 2, 273 Aboriginal and Torres Strait Islander (TSI) adults (18+ years) from 26 remote communities in far North Queensland, who were initially free of cancer, were followed‐up for an average of 15 years. The associations of baseline anthropometric, biochemical and behavioural factors with cancer incidence were investigated using competing risk survival analysis. The age‐standardised incidence (all cancers) was 5.2 cases/1, 000 person‐years (pys) (95% CI 4.1–6.6). Liver/bile duct and lung were the most common cancer sites. Overall cancer incidence was significantly higher in TSIs than Aboriginal people. The baseline prevalence of diabetes was 15.6% in Aboriginal and 25.6% in TSI people. The smoking rate of 59.8% for Aboriginal people was higher than the rate of 45.2% for TSIs. At follow‐up, the adjusted sub hazard ratios (SHRs) of diabetes for all cancers combined were 1.8 (95% CI, 1.3–2.6), and for digestive system cancers, 2.3 (95% CI, 1.2–4.4). Smokers had a 60% higher risk (SHR 1.6, 95% CI: 1.1–2.0) for all cancers combined and a fourfold risk (SHR 3.7, 95% CI 1.7–8.0) for lung cancers when compared to non‐smokers, regardless of age, sex and ethnicity. The most common cancers encountered by this Indigenous cohort and their consequences are potentially preventable in Indigenous Australians by effective management of highly prevalent modifiable risks in primary service settings, screening participation and arranging for good access to treatment services. Abstract : What's new? This is the first formal report of cancer incidence and associated biochemical and lifestyle risk factors in a 15‐year follow‐up of Indigenous Australians in remote North Queensland communities. Diabetes, and smoking, which are prevalent in the Indigenous communities, have been associated with cancer incidence. A four‐fold incidence of diabetes was found in this cohort compared with the general population, which was related to obesity and several metabolic risk factors. The most commonly encountered cancers and their consequences are potentially preventable in Indigenous Australians through effective management of highly prevalent modifiable risks, greater screening participation, and better access to treatment services.